2005
DOI: 10.1002/jclp.20101
|View full text |Cite
|
Sign up to set email alerts
|

Using the Conformity to Masculine Norms Inventory to work with men in a clinical setting

Abstract: Given that gender roles are increasingly viewed as salient in clinical work with men, this article describes a process of exploring masculine gender roles with male clients in therapy by using the Conformity to Masculine Norms Inventory (CMNI). Specifically, this article (a) discusses how men's degree of conformity to masculine norms may be connected to a variety of benefits and costs, (b) describes the CMNI as a tool that can be used to explore men's degree of conformity to masculine norms, (c) describes a pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
101
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(107 citation statements)
references
References 21 publications
5
101
0
1
Order By: Relevance
“…Conformity to masculine norms theory has identified a subset of dominant norms of traditional masculinity that are prevalent in American society: (a) Winning; (b) Emotional Control; (c) Risk-Taking; (d) Violence; (e) Power Over Women; (f) Playboy; (g) Self-Reliance; (h) Primacy of Work; and (i) Heterosexual SelfPresentation. Research in the psychological study of men and masculinity has demonstrated that conforming to traditional masculine norms can exact a cost on men and on others in men's lives (e.g., Burn & Ward, 2005;Liu & Iwamoto, 2007;Mahalik, Levi-Minzi, & Walker, 2007;Mahalik, Talmadge, Locke, & Scott, 2005;Parent & Moradi, 2009). Even though sport is believed to serve as a primary influence on young men's construction of masculinity (Martin & Harris, 2006;Messner, 1992;Wellard, 2002;Whannel, 2007), there has been a dearth of research into how masculine norms operate in sport.…”
Section: Conformity To Masculine Norms In Sportmentioning
confidence: 99%
“…Conformity to masculine norms theory has identified a subset of dominant norms of traditional masculinity that are prevalent in American society: (a) Winning; (b) Emotional Control; (c) Risk-Taking; (d) Violence; (e) Power Over Women; (f) Playboy; (g) Self-Reliance; (h) Primacy of Work; and (i) Heterosexual SelfPresentation. Research in the psychological study of men and masculinity has demonstrated that conforming to traditional masculine norms can exact a cost on men and on others in men's lives (e.g., Burn & Ward, 2005;Liu & Iwamoto, 2007;Mahalik, Levi-Minzi, & Walker, 2007;Mahalik, Talmadge, Locke, & Scott, 2005;Parent & Moradi, 2009). Even though sport is believed to serve as a primary influence on young men's construction of masculinity (Martin & Harris, 2006;Messner, 1992;Wellard, 2002;Whannel, 2007), there has been a dearth of research into how masculine norms operate in sport.…”
Section: Conformity To Masculine Norms In Sportmentioning
confidence: 99%
“…Given that expressions of masculinity are highly culturally dependent, examining differences across countries would provide important additional information about potential cultural meanings of masculinity in relation to male body ideals and appearance. Given this, our group recently examined the relationship between conformity to masculinity norms (CMN) and several measures of body image in Australia, Sweden, the UK, and the US (Holmqvist Gattario et al, in press), finding that higher CMN was not only associated with higher drive for muscularity, as reported in the literature (Mahalik, Talmadge, Locke, & Scott, 2005;Smolak & Murnen, 2008), but also predicted higher drive for leanness and fitness (Smolak & Murnen, 2008).…”
mentioning
confidence: 96%
“…The Conformity to Masculine Norms Inventory (CMNI) was developed to assess the extent to which a male conforms to major masculinity norms found in the dominant culture in the United States. The norms are: winning, emotional control, risk-taking, violence, dominance, playboy image, self-reliance, primacy of work, power over women, disdain for homosexuality, and pursuit of status (Mahalik & Talmadge, 2005). Men with higher levels of education represented lower scores of conformity to masculine norms (Reilly, Rochlen, & Awad, 2013).…”
Section: Caucasiansmentioning
confidence: 99%